Exploring Promoting Paid Polygamy Mentoring on Social Media: Between Piety, Ideologization, and Economic Purpose - Ula, Siti Khoirotul (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
The promotion of polygamy mentoring began in 2017 by several polygamy practitioners as an Islamic lifestyle among the urban middle class. This movement goes hand in hand with the hijrah movement, which is also increasingly popular among them. Polygamy is even openly promoted through high-cost mentoring courses. Starting from tens to hundreds of millions of rupiah. This article presents a qualitative research that employs the netnography method to investigate the promotion of paid polygamy mentoring on social media by Dauroh Poligami Indonesia (DPI), Forum Poligami Indonesia (FPI), and Private Mentor Coach Hafidin. This article aims to explore the goals and motives behind the promotion of paid polygamy mentoring conducted by the mentors. By observing their posts on social media and conducting interviews, this research found that the practice of promoting paid polygamy mentoring, which is a form of religious commodification, has several purposes for the mentors: fulfilling religious commandments (piety), increasing offspring and strengthening the power of Islam as well as engaging in jihad fi sabilillah (ideological goals), and achieving material gain (economic purposes). The author argues that the practice of religious commodification is not always aimed solely at generating economic profit, but in some cases also serves ideological and pious purposes. This research also corrects the studies by Ahmadi, Hasan, and Fealy, who argue that the practice of religious commodification is solely economically motivated. Based on this research case, the ideological and theological motives are also found in the practice of promoting paid polygamy mentoring on social media.